Tarefas informatizadas e jogos aplicados pelos pais na aprendizagem de leitura por crianças com transtorno do espectro autista - Menotti, Ana Rubia Saes (Universidade Federal de São Carlos, 2016)
A child with Autism Spectrum Disorder (ASD) can present difficulties in the acquisition of symbolic behavior in general, including in reading. Educational programs via computerized curriculum based on stimulus equivalence provide children opportunities to learn reading repertoire. This study aimed at the implementation and evaluation of a computerized procedure for teaching reading fifteen-syllable words (isolated) for children with ASD, based on stimulus equivalence paradigm. As a secondary goal of the study we built games to work at home, seeking parental involvement in reading learning of their children. In the study participated three autistic children and their parents. We used a multiple baseline design of sets of words, combined with pre and post-test. The procedure began with the implementation of the pre-test after conducting five stages of teaching and finally the post-test. In the five teaching steps, gaming sessions and teaching sessions of isolated words through computerized curriculum were performed. In general, the results showed that children made gains in the repertoire of reading, although they showed no generalization of learning to generalized reading significantly. Parents were involved in the application of games and used reinforcement and prompt during the sessions properly. Keywords: reading, computerized instruction, games, children with ASD, parents.
Computerized tasks and games applied by parents in learning reading by children with autism spectrum disorder.
Keywords: Leitura; Ensino informatizado; Jogos; Crianças com TEA; Pais; CIENCIAS HUMANAS::PSICOLOGIA